The quasi-static test of hollow prefabricated circular pier with high-strength reinforcement and calculation method for plastic hinge length. (March 2023) - Fu, Tao; Zhu, Zhixin; Ren, Xiaoqian; Li, Yan; Sun, Yue; Meng, Lingxiao; Sun, Zhonghua
Abstract: A high-strength hollow prefabricated circular pier with HTRB600E high-strength reinforcement was proposed to realise lightweight prefabricated piers and optimise their seismic performance. Its seismic performance was investigated by comparing and analysing the seismic performance indices of four different types of piers under low-cyclic reciprocating load. The finite element model (FEM) was used to analyse the influences of the grouted sleeve length, axial compression ratio, and longitudinal reinforcement strength on the equivalent plastic hinge length of the proposed pier. The equation for calculating the equivalent plastic hinge length under different working conditions was based on multiple linear regression. The results showed that different parameters had different degrees of influence on the plastic hinge length of the proposed pier, with the axial compression ratio having the strongest influence.